TREC and KREC Levels as a Predictors of Lymphocyte Subpopulations Measured by Flow Cytometry - Korsunskiy, Ilya; Blyuss, Oleg; Gordukova, Maria; Davydova, Nataliia; Gordleeva, Susanna; Molchanov, Robert; Asmanov, Alan; Peshko, Dmitrii; Zinovieva, Nataliia; Zimin, Sergey; Lazarev, Vladimir; Salpagarova, Aminat; et al. (Frontiers in Physiology, 2019)
Primary immunodeficiency diseases (PID) is a heterogeneous group of disorders caused by genetic defects of the immune system, which manifests clinically as recurrent infections, autoimmune diseases or malignancies. Early detection of other PID remains a challenge. Particularly in older children due to milder and less specific symptoms, a low level of clinician PID awareness and poor provision of hospital laboratories with appropriate devices. T-cell recombination excision circles (TREC) and kappa-deleting element recombination circle (KREC) in a dried blood spot and in peripheral blood using real-time polymerase chain reaction (PCR) are used as a tool for severe combined immune deficiency but not in PID. They represent an attractive and cheap target for a more extensive use in clinical practice. This study aimed to assess TREC/KREC correspondence with lymphocyte subpopulations, measured by flow cytometry and evaluate correlations between TREC/KREC, lymphocyte subpopulations and immunoglobulins. We carried out analysis of data from children assessed by clinical immunologists at Speransky Children’s Hospital, Moscow, Russia with suspected immunodeficiencies between May 2013 and August 2016. Peripheral blood samples were sent for TREC/KREC, flow cytometry (CD3, CD4, CD8 and CD19), IgA, IgM and IgG analysis. A total of 839 samples were analysed for using TREC assay and flow cytometry and 931 KREC/flow cytometry. TREC demonstrated an AUC of 0.73 (95% CI 0.70 – 0.76) for CD3, 0.74 (95% CI 0.71 – 0.77) for CD4 and 0.67 (95% CI 0.63 – 0.70) for CD8 respectively, while KREC demonstrated an AUC of 0.72 (95% CI 0.69 – 0.76) for CD19. Moderate correlation was found between the levels of TREC and CD4 (r=0.55, p<0.01) and KREC with CD19 (r=0.56, p<0.01). In this study, a promising prediction models were tested. We found that TREC and KREC are able to moderately detect abnormal levels of individual lymphocyte subpopulations. Future research should assess associations between TREC/KREC and other lymphocyte subpopulations and approach TREC/KREC use in PID diagnosis.